Propuesta de un sistema de producto – servicio para optimizar las actividades del proceso de consulta médica en una clínica pediátrica - Santillán Vásconez, Verónica Elizabeth (2019)
The present document is a methodological research work and solution of design needs focused on giving life and work quality to the humans involved in the pediatric care service. Through the design service of children’s health, arises not resolved problems, whose solutions are lying in the attentively listening of needs of the people involved. This is how children, parents and doctors have something to contribute in the creation of an experience that reaches the point of tangibility through the construction of the identity of the brand and the design of the products: The progressive web application (PWA), the pop-up book, the audio products, the calendar of the team, the stationery and merchandising products of the brand. These are meant to become tools for effective communication among them, into de three moments of the service; before the appointment, in the medical appointment, after the appointment. All of this whit the idea of harmonizing and bringing people closer in the use of the service though the concept of solidarity, who raised in a reunion of the group. That is why the methodological tools that were chosen were taken from organization approaches that focus on the human who receives care, the human who gives the care and the human accompanying it (the golden circle and the human centered design), from where creativity based on results acts. "Creativity is a way of understanding the world". David Kelley.